VD_FINDINFO Décision / 2012 / 149 vom 18. Februar 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, PROPORTIONNALITÉ, PRINCIPE DE LA CÉLÉRITÉ | 222 CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH), 5 CPP (CH)